KINERJA PANITIA PENGAWAS PEMILIHAN UMUM DALAM PENYELENGGARAAN PEMILIHAN UMUM CALON ANGGOTA LEGISLATIF DI PARIGI MOUTONG TAHUN 2014 - Idrus, Idrus (Katalogis, 2015)
Research on the performance of general election supervisory committee in general election of legislative candidates in Parigi Moutong District 2014 has been carried out since March 2015 to May 2015. This study aims at determining the performance of general election supervisory committee in general election of legislative candidates in Parigi Moutong District 2014. The data were analyzed by using an interactive model of Miles and Huberman. The result of this research shows that the performance of Election Supervisory Committee is not optimal seen from the aspects (1) productivity in terms of quantity and quality of the available documents in the office of the elections supervision is not completely legally, (2) The quality of services is not adequate because the election committees of Parigi Moutong district were not able to carry out their tasks optimally (3) Responsiveness. Supervisory Committees in carrying out a task did not provide their time optimally to serve the public yet. (4) Responsibility. Election Supervisory Committees handled various violations incompletely (5) Accountability. The committees were not able to carry out tasks completely. The authority of election committees is limited understanding and reporting any violations in any incidents, so that what is reported is not fully completed.